2023
DOI: 10.3390/en16135073
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the Scheduling of Electrified Public Transport System in Malta

Abstract: In this paper, we describe a comparative analysis of a bus route scheduling problem as part of timetable trips. We consider the current uptake of electric buses as a viable public transportation option that will eventually phase out the diesel-engine-based buses. We note that, with the increasing number of electric buses, the complexity related to the scheduling also increases, especially stemming from the charging requirement and the dedicated infrastructure behind it. The aim of our comparative study is to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Other approaches have been proposed to optimize bus schedules. For example, Sharma et al [17] proposed a multi-agent framework to plan the schedules of one-way routes in Malta, and it was shown that this has a better performance compared to the traditional approach using mixed integer linear programming. Another approach was proposed by Xue et al [18] in which they used uncertainty theory and a bilevel programming model to optimize the frequency and time between departures of the 207 bus routes of Nanchang city, China; they demonstrated that this is an effective approach for reducing passengers' travel times, but it has some limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Other approaches have been proposed to optimize bus schedules. For example, Sharma et al [17] proposed a multi-agent framework to plan the schedules of one-way routes in Malta, and it was shown that this has a better performance compared to the traditional approach using mixed integer linear programming. Another approach was proposed by Xue et al [18] in which they used uncertainty theory and a bilevel programming model to optimize the frequency and time between departures of the 207 bus routes of Nanchang city, China; they demonstrated that this is an effective approach for reducing passengers' travel times, but it has some limitations.…”
Section: Introductionmentioning
confidence: 99%